Free vibration of bimaterial split beam - Shu, D.; Fan, H.
The coupling between transverse and longitudinal vibration in an inhomogeneous beam has been formulated and discussed. A special case of bimaterial split beam is solved to show the effect of delamination on the natural frequency of the split beam, High sensitivity of the natural frequency towards the size and location of the delamination is displayed. In conjunction with other techniques, this sensitivity can be used to locate and determine the size of delaminations in beam plates during inspection.
Keywords: BIMATERIAL; COUPLING; VIBRATION; BEAM